Common injuries and conditions in rowers - Karlson, K. A.; Stone, G. L. (Endurance sports medicine, 2023)
Rowing is a repetitive sport, thus injuries in rowing are commonly the result of overuse, but also are the result of interaction with the equipment and rowing technique. Injuries to the back and rib are most common, but overuse injuries of the knee, shoulder, and forearm are also seen in rowing. Knowledge of the rowing stroke dynamics and what is alterable in terms of technique and equipment changes will help the clinician assist the injured rower.